Using Semantic Web to Improve accessibility to visually impaired users - Sorrentino, Tatiana Amaral (2018)
Web is a great resource and has become indispensable today. However, visually impaired users still face many difficulties in using the services available on the web. This paper presents experimental results of a semantic model that provides accessibility on websites for the visually impaired users. The model consists of components that do the page processing to prioritize relevant information and provide additional information so that the page elements become more understandable to this target public. One semantic enrichment strategy is used in the elements available to improve their understanding. The result is an adapted page according to the user's needs. The model is under development and has been partially implemented and validated in two scenarios. The main goal is to make Web navigation a more effective experience for the visually impaired. The results of the experiments are pages enriched with information especially adapted for blind people.